2018
DOI: 10.31234/osf.io/nb392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Which Group to Credit (and Blame)? Whites Make Attributions about White-Minority Biracials’ Successes and Failures Based on Their Own (Anti-)Egalitarianism and Ethnic Identification

Abstract: Individuals’ perceptions of biracials can vary based on the motives of the perceiver. Here, we examine how two factors—perceivers’ group-level identification motives and their system-level beliefs about the desirability of hierarchy (i.e., social dominance orientation)—predict the degree to which they attribute a biracial target’s successes or failures to that target’s White versus minority backgrounds. Across three studies examining different contexts, more anti-egalitarian White participants and (independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The present work suggests another reason: high and low SDO individuals may also come to display biased perceptions of the degree of hierarchy, which subsequently reinforce their convictions about the types of social policies they tend to favor. The notion of hierarchy-enhancing and attenuating perceptual biases is consistent with recent evidence that individuals’ SDO motives influence their perception of racially ambiguous targets in ways that help maintain or attenuate hierarchy (see Ho et al, 2013; Kteily et al, 2014; McClanahan, Kteily, & Ho, under review).…”
Section: Discussionsupporting
confidence: 75%
“…The present work suggests another reason: high and low SDO individuals may also come to display biased perceptions of the degree of hierarchy, which subsequently reinforce their convictions about the types of social policies they tend to favor. The notion of hierarchy-enhancing and attenuating perceptual biases is consistent with recent evidence that individuals’ SDO motives influence their perception of racially ambiguous targets in ways that help maintain or attenuate hierarchy (see Ho et al, 2013; Kteily et al, 2014; McClanahan, Kteily, & Ho, under review).…”
Section: Discussionsupporting
confidence: 75%
“…Some research has also examined the willingness to use the category multiracial (vs. monoracial categories; e.g., Chen & Hamilton, 2012; Chen et al, 2014; Gaither, Chen, et al, 2018; Pauker et al, 2018; Peery & Bodenhausen, 2008; see Chen, 2019, for a review) or the tendency to categorize multiracial people as non-White, but not necessarily as members of their minority parent group (when ancestry is unknown; Chen, Pauker, et al, 2018; Nicolas et al, 2019). Beyond categorization, one paper has also examined perceivers’ attributions about which of a multiracial person’s background was most formative, as a function of the motivation to raise the standing of one group versus another (McClanahan et al, 2019). It would be useful to identify intergroup motives and conditions that give rise to these categorization and attribution patterns too (e.g., if there are similarities to what drives outgroup categorization).…”
Section: Discussionmentioning
confidence: 99%
“…And, these authors also hypothesized and found that individuals higher in SDO were not responsive to the target conformity manipulation. Thus, Kteily et al demonstrate that by measuring multiple motives that theoretically can drive hypodescent, and by systematically manipulating situational or target characteristics that may interact with some motives but not others, researchers can gain theoretical clarity on which motives are uniquely responsible for hypodescent, and under what conditions (see also McClanahan et al, 2019, for a similar dissociation showing simultaneous and distinct effects of SDO and ethnic identification predicting attributions about biracial targets).…”
Section: Toward a Theoretical Integrationmentioning
confidence: 99%
“…Identification with the ingroup is underscored by an attachment to the ingroup and a motivation to behave in ways that protect its welfare. The more identified an individual is with the ingroup, the more they are likely to engage in pro‐ingroup behaviours (McClanahan et al, 2019). Concern about group survival and continuity is usually a foremost concern for constituent groups in multi‐group settings (Adebayo & Olonisakin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While identification with the ingroup theoretically and empirically has been linked to outgroup intolerance (Kende, Hadarics, & Szabó, 2018; McClanahan, Ho, & Kteily, 2019; Sherif, 1958), research has shown that this may not always be the case. The interdependence that characterises multi‐group societies necessitates outgroup tolerance to ensure the survival of all groups regardless of the rivalry that exists between them (Duckitt, Callaghan, & Wagner, 2005; Olonisakin, 2021; Tanaka, Tago, & Gleditsch, 2017).…”
Section: Introductionmentioning
confidence: 99%